Driving Waveform Design Based on Driving Process Fusion and Black Reference Gray Scale for Electrophoretic Displays - Wang, Li; Ma, Pengchang; Zhang, Jitao; Wan, Qiming (Frontiers in Physics, 2021)
Electrophoretic display (EPD) is a kind of paper display technology, which has the advantages of ultra-low power consumption and readability under strong light. However, in an EPD driving process, four stages are needed to finish the driving of a pixel: erase original images, reset to black state, clear to white state, and write a new image. A white reference gray scale can be obtained before writing a new image, and this driving process may too long for comfort of reading. In this paper, an EPD driving waveform, which takes the black state as the reference gray, is proposed to short the driving time. In addition, the rules of direct-current (DC) balance are also followed to prevent the charge from getting trapped in the driving backplane. The driving process is fused and there are two stages in the driving waveform: reset to black state, write the next image. Firstly, the EPD is written to a stable black state according to the original gray scale driving waveform and the black state is used as the reference gray for the next image. Secondly, the new image is written by the second stage of the new driving waveform. The experimental results show that the proposed driving waveform has a better performance. Compared with the traditional driving waveform which has four stages, the driving time of the new driving waveform is reduced by nearly 50%.